STUDY ON POSSIBILITY FOR THE UTILIZATION OF TECHNICAL, HYDROLYSIS, LIGNIN IN COMPOSITION OF MEDIUM DENSITY FIBERBOARD - Yotov, Nikola; Savov, Viktor; Petrin, Stoyko; Valchev, Ivo; Karatotev, Viktor (Innovation in Woodworking Industry and Engineering design, 2017)
In the present report is presented a study on the possibility for utilization of hydrolysis lignin in the composition of Medium Density Fiberboard. For the purpose of the study in laboratory conditions were produced boards with five percentages technical lignin in their composition and different quantity of phenol-formaldehyde resin. The main physical and mechanical properties of boards were determined, and they have been compared with those of boards without technical lignin. It is compared the visual appearance of MDF with and without technical lignin. On that base was accomplished an analysis of the results with proper conclusions.